HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP KEPATUHAN DALAM PELAKSANAAN VAKSIN (MR) MEASLES-RUBELLA DI WILAYAH KERJA PUSKESMAS MANDALA MEDAN TAHUN 2019 - Ilfa Hasibuan; Putri Yunita Pane; Pahala Maringan J. Simangunsong (JURNAL KESMAS DAN GIZI (JKG), 2020)
Measles is a highly contagious disease that is caused by a virus and is transmitted through coughing and sneezing. The effects of Measles are high fever, reddish patches on the skin (rashes) heal with coughs or colds and red eyes (conjunctivitis). This disease is very dangerous if treated with complications of pneumonia, diarrhea, meningitis, and can even cause death. Rubella disease is a disease similar to Measles that is transmitted through the respiratory tract when coughing or sneezing. MR vaccine (Measles Rubella) in the Mandala Puskesmas Area in 2019. This research is a quantitative study using cross sectional. The population in this study is mothers who have children and children. Based on monthly patient visits, 385 patients in Mandala Medan Health Center in 2019 The technique of collecting data is by observation and questionnaire. Analysis of the data used in this study was the Chi-Square test (95% CI). The results of the study stated that there was a significant relationship between maternal knowledge in the implementation of the MR (Measles Rubella) Vaccine in the Mandala Health Center Area Medan with a p value of 0,000 (<Î± = 0.05). There is a significant relationship between the attitude of mothers in the implementation of MR (Measles Rubella) Vaccine in Mandala Medan Puskesmas with a p value of 0.000 (<Î± = 0.05) MR (Measles Rubella) in the Mandala Puskesmas Region in Medan